KETERAMPILAN PENGELOLAAN KELAS GURU TK DI KELURAHAN SIMPANG BARU KECAMATAN TAMPAN KOTA PEKANBARU - Risma, Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study was to determine the skills of classroom management of a kindergarten teacher in kelurahan Simpang Baru kecamatan Tampan kotaPekanbaru. This is a descriptive study, the data was collected using a questionnaire-shaped instrument number 29 point statement. Once tested, the questionnaire is valid for 23 items and is not valid for 6 items. Overall a reliable instrument to